Peningkatan potensi pendapatan desa melalui pengelolaan tempat wisata serta kegiatan penghijauan pada Desa Selemak Kab. Deli serdang - Syamsul Bahri Surbakti; Akman Daulay; Sri Puspa; Sinto; Seniwati; Sukarsih; Muhammad Fazri (Jurnal Derma Pengabdian Dosen Perguruan Tinggi (Jurnal DEPUTI), 2024)
The Mandiri Program, a government initiative, aims to increase the potential of existing villages in Indonesia by focusing on their development and increasing their contribution to employment and community development. One such village is Selemak Village located in Deli Serdang, North Sumatra, and has a main water source called Taman Prima Wisata Edukasi. This water source is important for the community to maintain environmental health and increase cooperation among members, leaders, and stakeholders. Community development tasks include socialization to increase village water potential and carry out environmental conservation activities around the main water sources. The implementation of environmental conservation activities includes mapping, discussion, and conservation activities around the location of water sources. The main objective is to understand the potential of the village and its role in conservation efforts around the location of water sources